SUBTAWEE Transportation Management on Mobile Application - Nattaphorn Maliwan; Chonlada Maliwan; Rattapong Suwalak (My University, 2022)
This paper provides information about the design of the mobile application for transportation management. Initially, the user must be logged in to access the mobile application. It is divided into 3 access roles, i.e., 1) administrator can use job summary, time verification function, and driver function, 2) staff can use the driver’s time and time verification function, and 3) driver can use the job function. The application’s movement data since login. Confirmation of the time of the car leaving the plant. Job verification on behalf of the driver, including the driver confirming the customer submission, is stored in the entire database, which is notified every time it is logged in and when the work is sent to the customer via the Line Notification, as well as the daily revenue amount and monthly income is displayed. Displays within the proposed mobile application to keep drivers informed. The mobile application is convenient to use and work very well for the transportation management of the SUBTAWEE Concrete Company Langsuan Co., Ltd. This mobile application can be applied to the transportation management and the others similarly process.
Keywords: Service-Oriented Architecture and Web Services; Mobile Agent-Based Network Management; Mobile and Web Applications